Silicon-doped hydroxyapatite (at) MnO2 composite material as well as preparation method and application thereof
By doping silicon elements and forming silicon-doped hydroxyapatite @MnO2 composite materials, the problems of high cytotoxicity of pure MnO2 and slow degradation rate of hydroxyapatite are solved, and the effects of low cytotoxicity and significant thermal response performance are achieved. They are suitable for cancer treatment and magnetic resonance imaging.
Patent Information
- Application Number
- CN202411627896.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-03-07
AI Technical Summary
In the prior art, MnO2 is highly cytotoxic, while the degradation rate of hydroxyapatite is slow, which cannot effectively solve the problems of cytotoxicity and material degradation in cancer treatment.
By doping silicon elements, the crystal lattice structure of hydroxyapatite is changed, its stability is reduced, and the permanganate solution is reacted with a silicon-doped hydroxyapatite suspension to form a core-shell structure with silicon-doped hydroxyapatite as the core and MnO2 as the shell, and a silicon-doped hydroxyapatite@MnO2 composite material is prepared.
It reduces the cytotoxicity of MnO2, promotes the degradation of the material, imparts significant thermal response performance and magnetic resonance imaging functions to the composite material, and is suitable for photothermal therapy and nanocontrast agents.
Smart Images

Figure CN119569007A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of magnetic resonance imaging materials, and in particular to a silicon-doped hydroxyapatite@MnO2 composite material and a preparation method and application thereof. Background Art
[0002] Affected by environmental pollution and changes in people's lifestyles, cancer cases are increasing year by year, and cancer is increasingly threatening people's health. Existing cancer treatments mainly include surgery, chemotherapy, and radiotherapy, but these methods cannot completely eliminate cancer cells and can cause serious toxic side effects to normal tissues and cells of the body. It is understood that increased levels of intracellular glutathione (GSH) have been found in many tumor cells, such as bone cancer and head and neck cancer. Increased levels of intracellular GSH may cause cells to resist apoptosis. It is worth mentioning that alleviating hypoxia and GSH depletion can destroy the tumor microenvironment (TME) and the antioxidant defense system of cells.
[0003] Manganese has good biosafety and abundant valence states. It is one of the most commonly used metal elements in cancer treatment and can be used in the design and synthesis of smart therapeutic agents. For example, manganese dioxide is widely used as a mimetic of catalase to decompose hydrogen peroxide (H2O2) in the tumor microenvironment and produce oxygen, thereby alleviating tumor hypoxia and reducing tumor resistance to radiotherapy or chemotherapy.
[0004] In addition, it has been reported that Mn released from MnO2 2+ Mn can mediate a Fenton-like reaction, which can reduce the level of GSH in the tumor microenvironment to increase the level of reactive oxygen species (ROS). 2+ Directed chemodynamic therapy (CDT) further expands the potential of manganese as a nanomaterial. In addition, in addition to gadolinium contrast agents, manganese is one of the best alternative magnetic resonance contrast agents. The high resolution and unlimited penetration depth of magnetic resonance imaging can also make up for the lack of PAI imaging capabilities. Therefore, the development of MnO2 as a new multifunctional nanocontrast agent becomes possible. However, pure MnO2 has high cytotoxicity, and when used in high concentrations, it may also cause infectious bronchitis, pneumonia, and neuropsychiatric diseases (manganese poisoning).
[0005] Hydroxyapatite (HAp, (Ca 10 The chemical composition of (PO4)6(OH)2) is the same as the main inorganic mineral component of human bone tissue. It is widely used in bone defect repair due to its good biocompatibility, osteoconduction and osteoinduction ability. However, pure HAp has a slow degradation rate and is often covered by newly formed bone after implantation. It cannot mediate new angiogenesis or tissue ingrowth, which hinders the degradation and absorption of the material. Summary of the invention
[0006] The purpose of the present invention is to overcome the above technical deficiencies, provide a silicon-doped hydroxyapatite@MnO2 composite material and a preparation method and application thereof, and solve the technical problems in the prior art that pure MnO2 has high cytotoxicity and hydroxyapatite has slow degradation rate.
[0007] In order to achieve the above technical purpose, the technical solution provided by the present invention is: In a first aspect, the present invention provides a method for preparing a silicon-doped hydroxyapatite@MnO2 composite material, comprising the following steps: adding a permanganate solution to a silicon-doped hydroxyapatite suspension for reaction, wherein the mass ratio of the silicon-doped hydroxyapatite to the permanganate is (5-8.75): (0.01-0.024); after the reaction is completed, post-treatment is performed to obtain the silicon-doped hydroxyapatite@MnO2 composite material.
[0008] In a second aspect, the present invention provides a silicon-doped hydroxyapatite@MnO2 composite material prepared by the above preparation method.
[0009] In a third aspect, the present invention provides an application of the above-mentioned silicon-doped hydroxyapatite@MnO2 composite material in a thermal responsive material / photothermal therapeutic agent or nanocontrast agent.
[0010] Compared with the prior art, the beneficial effects of the present invention include: The present invention changes the lattice structure of hydroxyapatite by doping Si, reduces the stability of the structure, and thus promotes degradation; by doping a permanganate solution into a silicon-doped hydroxyapatite suspension for reaction, it can decompose and grow on the silicon-doped hydroxyapatite to form a core-shell structure with silicon-doped hydroxyapatite as the core and MnO2 as the shell. The resulting silicon-doped hydroxyapatite@MnO2 composite material has a uniform morphology, and by controlling the dosage ratio of permanganate and silicon-doped hydroxyapatite to form a uniform shell layer, it is ensured that the cytotoxicity is low or even non-cytotoxic, and has significant thermal response performance. It has been verified that the present invention uses silicon-doped hydroxyapatite as the core and deposits MnO2 on its surface. Under the same conditions, it not only reduces the cytotoxicity of pure MnO2, but also gives the material functionality (photothermal performance and magnetic resonance imaging function, etc.). BRIEF DESCRIPTION OF THE DRAWINGS
[0011] Figure 1 is a flow chart of Embodiment 1 of the present invention; Figure 2 1 is a SEM image of the silicon-doped hydroxyapatite powder (SiHA) and the silicon-doped hydroxyapatite@MnO2 composite material (SiHA@MnO2) obtained in Example 1 of the present invention; wherein A is SiHA and B is SiHA@MnO2; Figure 3The Mn content of the silicon-doped hydroxyapatite@MnO2 composite material (SiHA@MnO2) at different pH values in Example 1 of the present invention is 2+ Release curve; Figure 4 1 is a ROS fluorescence image of the silicon-doped hydroxyapatite@MnO2 composite material (SiHA@MnO2) and the control group (SiHA) in Example 1 of the present invention; wherein A is the control group and B is SiHA@MnO2; Figure 5 It is the near infrared temperature rise curve of the silicon-doped hydroxyapatite@MnO2 composite material (SiHA@MnO2) of Example 1 of the present invention and the control group (SiHA); Figure 6 It is the test result of the cytotoxicity test of the present invention. DETAILED DESCRIPTION
[0012] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0013] MnO2 is expected to be a new multifunctional nanocontrast agent, but pure MnO2 is highly cytotoxic and may cause infection or manganese poisoning when used in high concentrations. 10 The chemical composition of (PO4)6(OH)2) is the same as the main inorganic mineral component of human bone tissue. It is widely used in bone defect repair due to its good biocompatibility, osteoconduction and osteoinduction ability. However, pure HAp has a slow degradation rate and is often covered by newly formed bone after implantation. It cannot mediate new angiogenesis or tissue growth, which hinders the degradation and absorption of the material.
[0014] Silicon has a multifunctional effect in regulating bone metabolism. While promoting osteogenesis and angiogenesis, it also has the effect of inhibiting osteoclastogenesis and local immune regulation. At the same time, the present invention changes the lattice structure of hydroxyapatite by doping with Si, reduces the stability of the structure, and thus solves the problem of slow degradation of hydroxyapatite itself. Therefore, the silicon-doped hydroxyapatite formed by modifying hydroxyapatite and doping it with elements has broad application prospects.
[0015] In a first aspect, the present invention provides a method for preparing a silicon-doped hydroxyapatite@MnO2 composite material, comprising the following steps: adding a permanganate solution into a silicon-doped hydroxyapatite suspension to react, wherein the mass ratio of the silicon-doped hydroxyapatite to the permanganate is (5-8.75): (0.01-0.024); After the reaction is completed, silicon-doped hydroxyapatite@MnO2 composite material is obtained through post-treatment.
[0016] In the present invention, permanganate is used as a manganese source; its content will affect the thickness of the MnO2 layer in the final silicon-doped hydroxyapatite@MnO2 composite material. Too much content will make the layer thickness too high and produce certain cytotoxicity; too little content will make the layer thickness too low and fail to achieve significant thermal response and imaging effects.
[0017] Preferably, the concentration of the permanganate solution is 0.5-1.2 mg / mL.
[0018] Preferably, the permanganate includes potassium permanganate. In the present invention, potassium permanganate is used as a manganese source, and the manganese source is decomposed to grow on silicon-doped hydroxyapatite (SiHA), forming a core-shell structure with silicon-doped hydroxyapatite (SiHA) as a core and MnO2 as a shell; and the shell layer is formed in the form of growth, and the shell layer will be more uniform.
[0019] Preferably, the silicon-doped hydroxyapatite suspension is prepared by mixing silicon-doped hydroxyapatite with water; the mass concentration of the silicon-doped hydroxyapatite suspension is 20-35wt%.
[0020] Preferably, the preparation steps of silicon-doped hydroxyapatite specifically include: (1) adding a calcium source and a silicon source into water to dissolve, and heating and premixing to obtain a mixed solution A; (2) Adding an alkali-containing phosphorus source solution to the mixed solution A and stirring the mixture for reaction; after the reaction is completed, the mixture is placed for aging, solid-liquid separation, washing, drying, grinding and screening to obtain silicon-doped hydroxyapatite. In the present invention, the particle size of the silicon-doped hydroxyapatite is reduced by grinding and screening, for example, through a 100-mesh sieve, so as to increase the contact area and achieve a better coating effect.
[0021] Further preferably, the calcium source includes calcium chloride, the silicon source includes tetraethyl orthosilicate, the phosphorus source includes disodium hydrogen phosphate dodecahydrate, and the alkali includes sodium hydroxide; the calcium source is calculated as Ca element, the silicon source is calculated as Si element, and the phosphorus source is calculated as P element. The molar ratio of Ca / (Si+P) is 5:3, and the molar ratio of Si / (Si+P) is (2-6):100.
[0022] Further preferably, in step (1), the heating premix is stirred at 70-90° C. for 1-3 h; in step (2), the stirring reaction is stirred at 70-90° C. for 2-5 h; and the standing aging time is more than 15 h.
[0023] Further preferably, the mass ratio of the total mass of the calcium source and the silicon source to water is 1:(16-22); the alkaline phosphorus source solution is obtained by uniformly mixing the alkali and the phosphorus source with water, wherein the mass ratio of the total mass of the alkali and the phosphorus source to water is 1:(8-12).
[0024] Preferably, the reaction is carried out at room temperature and under ultrasonic conditions for 1 to 24 hours, and specifically, the reaction time can be selected from 1 hour, 3 hours, 6 hours, 8 hours, 9 hours, 10 hours, 12 hours, 14 hours, 16 hours, 18 hours, 20 hours, 22 hours or 24 hours. Temperature and time affect the effect of the MnO2 layer, wherein too high a temperature will cause potassium permanganate to decompose quickly, but the coating will not be uniformly formed; the present invention achieves the best effect by matching the appropriate time and temperature.
[0025] Preferably, the post-treatment includes centrifugal separation, washing, drying and grinding and screening; the centrifugal separation is performed at 5000-8000 rpm for 7-13 minutes; and the screening is performed using a 100-mesh sieve, that is, the particle size of the silicon-doped hydroxyapatite@MnO2 composite material is less than 150 microns.
[0026] In a second aspect, the present invention provides a silicon-doped hydroxyapatite@MnO2 composite material prepared by the above preparation method.
[0027] In a third aspect, the present invention provides an application of the above-mentioned silicon-doped hydroxyapatite@MnO2 composite material in the preparation of thermal responsive materials / photothermal therapeutic agents or nanocontrast agents.
[0028] After testing, the silicon-doped hydroxyapatite@MnO2 composite material prepared by the present invention has low cytotoxicity. Therefore, the manganese dioxide nanostructure can be used as a therapeutic diagnostic agent or nanocontrast agent responsive to TME. A large amount of high-concentration GSH in the tumor can also react with MnO2 to generate oxidized glutathione (GSSH). The concentration of GSH decreases and the generated Mn 2+ , which can not only perform MRI imaging, but also react with excess hydrogen peroxide in the tumor to generate hydroxyl free radicals, thereby enhancing chemodynamic therapy.
[0029] The method of the present invention has mild reaction conditions, and the prepared silicon-doped hydroxyapatite@MnO2 composite material has a microscopic morphology of SiHA@MnO2 nanocomposite nanoparticles with uniform morphology and strong near-infrared absorption ability, which can effectively convert the energy of near-infrared light into heat. 2 ) irradiated with 1064nm laser for 120s, and the temperature rose by 30.9℃, which was enough to kill cancer cells for photothermal therapy.
[0030] The present invention is further described in detail below through specific examples and comparative examples.
[0031] Example 1 A method for preparing silicon-doped hydroxyapatite@MnO2 composite material, see Figure 1 , including the following steps: S1. Preparation of silicon-doped hydroxyapatite: S11, weigh 1 mol of anhydrous calcium chloride and 0.028 mol of tetraethyl orthosilicate (TEOS), add a certain amount of purified water to dissolve, the total mass of anhydrous calcium chloride and TEOS: the mass of purified water = 1:20, add the solution into the reactor with mechanical stirring and heat to about 80°C, pre-mix for 3h, and obtain a mixed solution A; Weigh 0.572 mol of disodium hydrogen phosphate dodecahydrate and 0.9 mol of sodium hydroxide, add a certain amount of purified water to dissolve, the total mass of disodium hydrogen phosphate dodecahydrate and sodium hydroxide: the mass of purified water = 1:10, and stir thoroughly to obtain an alkaline phosphorus source solution.
[0032] S12, slowly drop the alkaline phosphorus source solution into the mixed solution A for reaction, continue stirring at about 80°C and 155r / min for 4h, and then the reaction is finished; turn off the heating and stirring, let it stand for at least 24h, discard the supernatant, collect the precipitate, filter it under positive pressure, and wash it repeatedly with purified water. Dry the precipitate at 60°C to constant weight, grind and screen it, and obtain silicon-doped hydroxyapatite powder (SiHA).
[0033] S2. Preparation of silicon-doped hydroxyapatite@MnO2 composite material: S21, prepare 25mL 30wt% SiHA suspension for standby use; S22. Add 20 mL (0.8 mg / mL) potassium permanganate solution to the SiHA suspension, place in an ultrasonic bath for 12 h, centrifuge at 8000 rpm for 10 min, discard the supernatant, wash with purified water for multiple times, dry in a vacuum oven at 60 °C to constant weight, grind and screen to obtain silicon-doped hydroxyapatite@MnO2 composite material (SiHA@MnO2).
[0034] The product obtained in this example was subjected to the following tests.
[0035] (1) SEM image: Figure 2 As shown, Figure A is the SEM image of SiHA synthesized in Example 1. It can be observed from the figure that SiHA presents a uniform rod-like structure with a size of about 200nm, specifically, a length between 200~250nm, and a diameter between 50~100nm; Figure B is the SEM image of SiHA@MnO2. It can be observed that SiHA is used as the core and the surface is uniformly covered with a layer of MnO2, and the coating thickness is between 100~150nm.
[0036] (2) In vitro Mn 2+Release: SiHA@MnO2 aqueous solution (1 mL, 5 mg / mL) was placed in a dialysis bag (MWCO=3600), and then the dialysis bag was placed in 49 mL of sodium hydrogen phosphate / citrate buffer (pH=7.4 and 6.5) with different pH values to simulate different biological environments. Continuous stirring was performed at room temperature. 0.5 mL of solution was taken outside the dialysis bag and Mn was determined by ICP-AES at 1, 2, 4, 8, 12, and 24 h. 2+ ion concentration, and add 0.5mL buffer to keep the volume constant. Figure 3 shown.
[0037] Depend on Figure 3 It can be seen that after incubation in an acidic buffer solution with pH = 6.5 for 12 h, more than 65% of the Mn 2+ It was released from SiHA@MnO2, but only about 10% in a neutral buffer solution of pH=7.4; such results indicate that the composite material of the present invention is beneficial for achieving better relief and treatment effects against acidic tumor environments.
[0038] (3) The production of reactive oxygen species in vitro was measured using the reactive oxygen species fluorescent probe DCFH-DA. U87MG cells were cultured with 20 μg / mL SiHA@MnO2 samples for 2 h, and then DCFH-DA (10 μM) was added. After 30 minutes of culture, the cells were washed with PBS and then observed using a fluorescence microscope (λex = 480 nm, λem = 525 nm). The results are shown in Figure 2. Figure 4 shown.
[0039] Depend on Figure 4 It can be seen that Figure A is the fluorescence image of SiHA synthesized in Example 1. There is no obvious fluorescence in the figure, indicating that SiHA has no obvious oxidative stress ability; Figure B is the fluorescence image of SiHA@MnO2, and obvious fluorescence appears in the figure. This is because DCFH hydrolyzed from DCFH-DA is oxidized by the active oxygen in the cells to generate fluorescent DCF, indicating that SiHA@MnO2 has a strong oxidative stress ability.
[0040] (4) Near-infrared absorption: The SiHA@MnO2 obtained in Example 1 was used as the experimental group, and the SiHA synthesized in Example 1 was used as the control group. The experimental group and the control group samples were placed in near-infrared (1064 nm, 0.5 W / cm 2 ) for 5 minutes, record the current temperature every 10 seconds, and finally draw a heating curve. The results are as follows Figure 5 shown.
[0041] Depend on Figure 5 It was found that at the safe power density of 1064nm laser (0.5W / cm 2) irradiation, an in vitro photothermal test was carried out for 120 seconds. The temperature of the experimental group rose by 30.9°C, while there was no obvious change in the control group, indicating that the SiHA@MnO2 composite material obtained by the present invention can be used as a photothermal therapeutic agent to kill cancer cells.
[0042] Comparative Example 1 The only difference from Example 1 is that the concentration of the potassium permanganate solution is adjusted to 0.4 mg / mL, and the other steps and conditions are the same as those in Example 1.
[0043] The results showed that when the concentration of potassium permanganate solution was too low, its dosage was insufficient, making the MnO2 coating too thin and uneven, thus failing to achieve the magnetic resonance imaging and photothermal effects.
[0044] Comparative Example 2 The only difference from Example 1 is that the concentration of the potassium permanganate solution is adjusted to 1.5 mg / mL, and the other steps and conditions are the same as those in Example 1.
[0045] The results showed that when the concentration of potassium permanganate solution was too high, it resulted in excessive usage, making the MnO2 coating too thick, and the coating would easily fall off during the cleaning process, resulting in uneven coating.
[0046] It can be seen from Example 1 and Comparative Examples 1-2 that too much or too little potassium permanganate will cause the coating to be too thick and easy to fall off, and too little coating will not achieve the defects of imaging and photothermal effects. Therefore, the preferred mass ratio of SiHA to potassium permanganate in the present invention is 7.5: (0.01-0.024).
[0047] Comparative Example 3 The only difference from Example 1 is that potassium permanganate is replaced by MnO2, and the other steps and conditions are the same as those in Example 1.
[0048] The results showed that directly using MnO2 as the manganese source, where MnO2 is insoluble in water, showed that MnO2 and SiHA were simply physically mixed, and the effect of MnO2 being uniformly coated on the surface of SiHA could not be achieved.
[0049] Cytotoxicity assay: Take the samples of Example 1, Comparative Example 1, Comparative Example 2, SiHA and MnO2 and sterilize them. Use DMEM culture medium as the extraction medium, with an extraction ratio of 0.2 g / mL, and extract at 37°C for 24 hours. After the extraction is completed, filter the extract and place it aside for later use. 5cell / 100μL was added to a 96-well plate, and 5 parallel samples were set for each sample, plus a positive control (10% DMSO), a negative control (PE material) and a blank control group; after culturing for 24 hours, the DMEM culture medium was aspirated. 100μL of treatment culture medium containing 100% concentration sample extract, positive control sample (10% DMSO), negative control extract (extraction conditions are the same as those of samples in Example 1) and medium (blank) control group was added to each well (that is, DMEM culture medium was directly added to the blank group). After incubation at 37°C, 5% CO2 incubator for 24 hours. Aspirate the culture medium in the well plate, add 100μL of DMEM culture medium and CCK8 mixture (10:1) to each well, incubate at 37°C for 1 hour, and measure the absorbance at 450 nm. The results are as follows Figure 6 shown.
[0050] Depend on Figure 6 It can be seen that under the same conditions (0.2 g / mL extraction), the SiHA sample has no cytotoxicity (cell survival rate is as high as 98.21%), and the pure MnO2 sample has high cytotoxicity (cell survival rate is only 15.73%); combining them according to the special ratio of the present invention can not only solve the cytotoxicity problem, but also give the material corresponding properties, such as photothermal properties and magnetic resonance imaging functions.
[0051] The specific implementation of the present invention described above does not constitute a limitation on the protection scope of the present invention. Any other corresponding changes and modifications made based on the technical concept of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A method for preparing a silicon-doped hydroxyapatite@MnO2 composite material, characterized in that: The following steps are involved: adding a permanganate solution into a silicon-doped hydroxyapatite suspension to react, wherein the mass ratio of the silicon-doped hydroxyapatite to the permanganate is (5-8.75): (0.01-0.024); After the reaction is completed, silicon-doped hydroxyapatite@MnO2 composite material is obtained through post-treatment.
2. The method for preparing the silicon-doped hydroxyapatite@MnO2 composite material according to claim 1, characterized in that: The concentration of the permanganate solution is 0.5-1.2 mg / mL; the permanganate includes potassium permanganate.
3. The method for preparing the silicon-doped hydroxyapatite@MnO2 composite material according to claim 1, characterized in that: The silicon-doped hydroxyapatite suspension is prepared by mixing silicon-doped hydroxyapatite with water; the mass concentration of the silicon-doped hydroxyapatite suspension is 20-35wt%.
4. The method for preparing the silicon-doped hydroxyapatite@MnO2 composite material according to claim 1, characterized in that: The preparation steps of the silicon-doped hydroxyapatite specifically include: (1) adding a calcium source and a silicon source into water to dissolve, and heating and premixing to obtain a mixed solution A; (2) Add an alkali-containing phosphorus source solution to the mixed solution A and stir to react; after the reaction is completed, the mixed solution is placed for aging, solid-liquid separation, washed, dried, ground and screened to obtain silicon-doped hydroxyapatite.
5. The method for preparing the silicon-doped hydroxyapatite@MnO2 composite material according to claim 4, characterized in that: The calcium source includes calcium chloride, the silicon source includes tetraethyl orthosilicate, the phosphorus source includes disodium hydrogen phosphate dodecahydrate, and the alkali includes sodium hydroxide; the calcium source is calculated as Ca element, the silicon source is calculated as Si element, and the phosphorus source is calculated as P element. The molar ratio of Ca / (Si+P) is 5:3, and the molar ratio of Si / (Si+P) is (2-6):
100.
6. The method for preparing the silicon-doped hydroxyapatite@MnO2 composite material according to claim 4, characterized in that: In step (1), the heating premixing is stirring at 70 to 90° C. for 1 to 3 hours; In step (2), the stirring reaction is carried out at 70-90° C. for 2-5 hours; and the standing aging time is more than 15 hours.
7. The method for preparing the silicon-doped hydroxyapatite@MnO2 composite material according to claim 1, characterized in that: The reaction is carried out at room temperature and under ultrasonic conditions for 1 to 24 hours.
8. The method for preparing the silicon-doped hydroxyapatite@MnO2 composite material according to claim 1, characterized in that: The post-treatment includes centrifugal separation, washing, drying and grinding and screening; the centrifugal separation is centrifugal separation at 5000-8000 rpm for 7-13 minutes.
9. The silicon-doped hydroxyapatite@MnO2 composite material prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the silicon-doped hydroxyapatite@MnO2 composite material as claimed in claim 9 in the preparation of thermal response materials / photothermal therapeutic agents or nano contrast agents.
Citation Information
Cited By
Silicon-doped hydroxyapatite composite biological ceramic material and application thereof
CN121313957A